Mortality among infants with congenital malformations, New York State, 1983 to 1988. - Druschel, C (1996)
OBJECTIVE. The authors examined first-year mortality and risk factors for mortality among infants with major congenital malformations. METHODS. Infants with major congenital malformations born from 1983 to 1988 were identified from a statewide population-based congenital malformations registry. Variables analyzed included year of birth, birth weight, gestational age, infant sex, number of malformations, number of organ systems involved, level of care of the birth hospital, maternal age, maternal education, and maternal ethnicity. RESULTS. Infants with major malformations had a risk of death 6.3 times higher than the general population of live births. The risk declined from 6.5 in 1983 to 5.9 in 1988. Birth weight and number of malformations were the strongest risk factors. The likelihood of survival was similar for white and black infants. CONCLUSIONS. Being born with a malformation outweighs most of the other risks for infant mortality. Children with congenital malformations had higher cause-specific mortality for all causes except injury.